Prevention of Osteoarthritis Progression by Statins, Targeting Metabolic and Inflammatory Aspects: A Review - Behzad Heidari (PCO Convin S.A., 2021)
Background and purpose: Several traditional risk factors of atherosclerosis such as age, obesity, and altered lipid metabolism are shared with osteoarthritis (OA). Metabolic abnormalities and atheromatous vascular disease are linked with systemic inflammation and progression of OA. Hence, treatment of OA with statins is expected to improve metabolic abnormalities and prevent OA progression. Many studies which have addressed this issue found inconsistent results. This review aims to elucidate the effect of statins in OA by summarizing the existing data. Methods: Potential studies in English language published in Medline/PubMed, Scopus and Google Scholar since 2000 were searched by using keywords such as osteoarthritis, statins, progression, treatment, prevalence, synovitis, pain. Fourteen papers were found to be relevant and were summarised. Results: Data regarding symptomatic effect of statins in OA are scarce and the results varied from no effect to a small improvement or even increased risk of pain in knee OA. However, most studies on the incidence and progression of OA found a significant decreased risk of incident OA, as well as reduced risk of radiographic progression in statin users vs. non-users. Factors such as patient adherence, duration of treatment, and higher cumulative statin doses were associated with greater efficacy. Conclusion: Existing data indicate a preventing effect of statin therapy on OA progression. However, unless a formal meta-analysis with weight analysis is made, a conclusion cannot be drawn.